Application of Big Data Analytics to Consolidate Fertilizer Trial Data into a Farmer-Support Tool - CGIAR Research Program on Water, Land and Ecosystems (2019)
We have influenced and supported the Ministry of Agriculture to develop and launch soils/agronomy data sharing policy for the first time. Currently, CIAT/WLE, GIZ and partners in collaboration with CABI are developing a guideline to support implementation of the policy. We are also advancing to develop site- specific fertilizer recommendation.